Ettling, Georg Friedrich Ludwig (1873-1942) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Lahusen, Christoph Friedrich (1851-1927) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Hoesch, Karl Albert Alexander (1847-1898) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Krummacher, Emil Wilhelm (1798-1886) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Olimart, Franz (1869-1943) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Keßler, Gerda, geb. Bertram (1911-1983) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Brevier fürs Revier. Mit der Bibel durch RUHR.2010

Siemoneit, Hans Rudolf (1927-2009) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Hüsch, Hanns Dieter (1925-2005) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Rutenborn, Günter (1912-1976) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Bernds, Heinrich (1901-1945) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Paskert, Ruth (1910-2004) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Wir werden aber alle verwandelt werden. Handreichung zu den "Local Hero Wochen" in der Kulturhauptstadt RUHR 2010 - Mawick, Gudrun; von Melle, Sebastian; Reichlung, Philipp E.; Schroeter-Wittke, Harald

Die gegenwärtige Praxis des Abendmahls. Bedingungen - Herausforderungen - Perspektiven - Schroeter-Wittke, Harald (Praktische Theologie)

Multikulturelle Urgeschichte. Zur Genesis-Suite von 1945 aus Hollywood - Schroeter-Wittke, Harald (Praktische Theologie)

Four Biblical Dances. Zum 80. Geburtstag von Petr Eben - Schroeter-Wittke, Harald (Praktische Theologie)

Abendmahl

Ja, wo singen sie denn? - Schroeter-Wittke, Harald (Junge Kirche)

Die Propheten im Aufbau der Bibel - Schroeter-Wittke, Harald (Erziehen heute)

Silent Night - X-mas Jazz - Schroeter-Wittke, Harald (Praktische Theologie)

Kristian Fechtner: Im Rhythmus des Kirchenjahres. Vom Sinn der Feste und Zeiten, Gütersloh 2007 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Klaus Kirchhoff: das gewisse Etwas. Phänomenologische Ansätze der Religionspädagogik - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Andrea Bieler / Luise Schottroff: Das Abendmahl. Essen, um zu leben. Gütersloh 2007 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

13. Sonntag nach Trinitatis. Lk 10,25-37: Eine überfallartige Geschichte, oder: Lesen, als ob das Leben davon abhinge - Schroeter-Wittke, Harald; Kirsner, Ing (Predigtstudien I/2)

Invokavit. Lk 4,1-13: Die zarteste Versuchung, seit es Kohle gibt - Schroeter-Wittke, Harald (Brevier fürs Revier)

Sexagesimae. Hebr 4,12f: Lebendig und kräftig und schwerter - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Lauter Hoffnung - Hoffnung lauter. Ein vierstimmiger Akkord aus dem 1. Petrusbrief - Schroeter-Wittke, Harald (Krichentagssonntag 31. Januar 2010)

Mit Gott lässt sich nicht rechnen - aber spielen! - Schroeter-Wittke, Harald (Text-Raum)

7. Sonntag nach Trinitatis. Joh 6,1-15: Christliche Zeichensetzung, oder: Abendmahl mit Aussetzungsworten - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Anticrossing of Whispering Gallery Modes in Microdisk Resonators Embedded in a Liquid Crystal - Förstner, Jens; Declair, S.; Meier, Cedrik; Meier, Torsten (Theoretical and Computational Nanophotonics Tacona-Photonics)
We numerically investigate Whispering Gallery Modes (WGM) in a subwavelength microdisk resonator [1] embedded in an uniaxial anisotropic liquid crystal environment. It is shown that the WGMs have anticrossing behavior when modes of different radial mode order M or azimuthal order N approach each other spectrally.
Keywords: tet_topic_microdisk

Coherent control in hybrid metal-semiconductor nanostructures - Meier, Torsten; Reichelt, Matthias (DPG Spring meeting 2009)
Recently it has been shown experimentally that it is possible to coherently control nano-optical excitations by using sophisticated shaped laser pulses. In this work a similar technique is used to theoretically investigate a hybrid nanostructure which consists of a metal aperture and a quantum wire. It is shown that one can concentrate the optically excited electron density at an arbitrary position due to wave packet dynamics by chosing particular frequency components and phases of the chirped laser pulse. The optimization process is performed with a genetic algorithm which is linked to a 3D-FDTD solver.

Shaping the spatiotemporal dynamics of the electron density in a hybrid metal-semiconductor nanostructure - Reichelt, Matthias; Meier, Torsten (Optics Letters)
A one-dimensional semiconductor nanostructure is locally excited through a metal aperture. It is shown that the electron density can be coherently localized at desired spatial and temporal positions by using nontrivially shaped laser pulses. To obtain the optimized laser field, Bloch equations for a tight-binding model system are solved together with a genetic pulse-shaping algorithm. Full three-dimensional finite-difference time-domain (FDTD) simulations of the Maxwell–Bloch equations confirm the predicted coherent spatiotemporal control.

Generation of injection currents in (110)-oriented GaAs quantum wells: experimental observation and development of a microscopic theory - Bieler, M.; Pierz, K.; Siegner, U.; Dawson, P.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIII)
We have experimentally investigated injection currents generated by all-optical excitation of GaAs/AlGaAs quantum wells excited with 130 fs optical pulses. The currents have been detected via free-space THz experiments at room temperature. Our experiments prove that Coulomb effects strongly influence injection currents. This becomes most prominently visible when exciting light-hole exciton transitions. At this photon energy we observe a pronounced phase shift of the current transients which is due to oppositely oriented heavy-hole and light-hole type contributions. We are currently developing a microscopic theory based on a 14×14 k.p model in combination with the semiconductor Bloch equations to describe the observed features quantitatively. The combined theoretical and experimental approach will allow us to analyze the influence of the bandstructure and interaction effects on the injection current amplitude and current dynamics.
Keywords: tet_topic_qw

Microscopic theory of the linear and nonlinear Terahertz response of semiconductors - Meier, Torsten; Koch, S.W.; Kira, M.; Steiner, J.T.; Golde, D. (CLEO/Europe - EQEC 2009 - European Conference on Lasers and Electro-Optics and the European Quantum Electronics Conference)
The paper presents a theoretical analysis of the nonlinear THz response from the internal transitions of coherent and incoherent excitons based on the formulated microscopic THz theory. Moreover, the response of unexcited semiconductors to extremely intense THz fields is investigated .The intersubband transitions of optically excited quantum wells using linear THz spectroscopy is also studied. The computed differential transmission shows a characteristic Fano-like line shape of the intersubband resonance. The pure intersubband contribution is given by a simple Lorentzian. Applying the microscopic theory, the Fano features of the total response can be attributed to the phase-sensitive superposition of the intersubband transitions and the ponderomotive contribution. These results are in excellent agreement with recent experiments.

Ultrafast coherent photoelectron emission effects and their application for time-domain studies of current transport - Meier, Torsten; Koch, S.W.; Rohleder, M.; Gudde, J.; Hofer, U. (Conference on Lasers and Electro-Optics and 2009 Conference on Quantum electronics and Laser Science Conference)
By combining coherent control schemes and photoelectron spectroscopy it is possible to generate ultrafast current pulses at surfaces and in solids and to detect their decay directly in momentum space with femtosecond time resolution.

Determination of homogeneous and inhomogeneous broadenings of quantum-well excitons by 2DFTS: An experiment-theory comparison - Kuznetsova, Irina; Thomas, Peter; Meier, Torsten; Zhang, Tianhao; Cundiff, Steven T. (physica status solidi (c))
The recently developed two-dimensional Fourier-Transform-Spectroscopy (2DFTS) in the optical regime has been established as an elegant experiment, which has manifold of applications in the investigation of semiconductor nanostructures. Here we focus on the real and imaginary part 2DFT spectra. As predicted recently, using rephasing and non-rephasing modes, we are able to determine the homogeneous and inhomogeneous broadenings of coupled excitonic resonances even for weak disorder where photon-echo data are not useful. Computed real and imaginary parts of the 2DFTS for rephasing and non-rephasing modes are compared with experimental data of a GaAs quantum well. It is demonstrated, that phase sensitive data for the rephasing and non-rephasing modes are able to accurately provide the disorder induced broadening in a complex coupled system for each transition separately.

Microscopic analysis of high-harmonic generation in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (physica status solidi (c))
A microscopic analysis of the emitted radiation of a semiconductor nanostructure after excitation with an extremely intense ultrashort laser pulse is presented. It is shown that the extreme nonlinear optical response is not sufficiently described by pure interband transitions but one has to include intraband effects as well. Numerical solutions of extended Bloch equations that include the coupled inter- and intraband dynamics are presented. For large excitation intensities, the intraband effects strongly modify the polarization dynamics and lead to a strong enhancement of high-harmonic generation compared to pure interband dynamics.

Preface - Meier, Torsten; Michler, Peter (physica status solidi c)

Reiseprosa zwischen erlebter und erfundener Erfahrung von Wolfgang Büscher, Hape Kerkeling und Sigrid und Hamster Damm - Müller, Inez (Autobiographisches Schreiben in der deutschsprachigen Gegenwartsliteratur, Bd. 3: Entwicklungen, Kontexte, Grenzgänge.)

Photo-and spin current generation and dynamics in semiconductor nanostructures - Meier, Torsten; Duc, Huynh Thanh; Foerstner, Jens (DPG Spring meeting 2009)
The band structure and wave functions of GaAs quantum wells are computed via k.p band structure theory including anisotropy and spin splitting. Using these results, the process of generating photocurrents by optical excitation is analyzed. Depending on the symmetry of the material, the direction of the laser beam, and the polarization direction of the light field/s, one can coherently generate charge and/or spin photocurrents on ultrashort time scales. The direction, the strength, and the dynamics of these photocurrents are computed and discussed.

Datenbilder. Zur digitalen Bildpraxis in den Naturwissenschaften - Adelmann, Ralf; Frercks, Jan; Heßler, Martina; Hennig, Jochen

Rezension zu: Hüppauf, Bernd; Weingart, Peter (Hrsg.): Frosch und Frankenstein. Bilder als Medium der Popularisierung von Wissenschaften. Bielefeld 2009 - Adelmann, Ralf (H-Soz-u-Kult)

Selbst etwas tun. Handeln und Subjektkonstitution in Computerspielen (Vortrag an der HBK Braunschweig 9.2.2009) - Adelmann, Ralf; Winkler, Hartmut

Geschichten einfliegen? Dynamische Einstellungen in Film und Fernsehen - Adelmann, Ralf (Fasten Your Seatbelt! Bewegtbilder vom Fliegen)

Zurück zur Meisterlehre? Beurteilen lernen und beurteilt werden am Ausbildungsort Schule - Freitag, Christine (Seminar – Lehrerbildung und Schule 3/2009)

Wirkungen digitaler Medien - Herzig, Bardo; Grafe, S. (Schule in der digitalen Welt)

Selbstreguliertes Lernen fördern. - Herzig, Bardo; Aßmann, S.; Altmann, R. (mathematik lehren. Begriffe klären, Konzepte entwickeln, Schule verändern.152 (2009))

Gestaltung von Unterricht. Eine Einführung in die Didaktik - Tulodziecki, G.; Herzig, Bardo; Blömeke, S.

Unexpected Hydrogen Bond Dynamics in Imidazolium-Based Ionic Liquids - Thar, J.; Brehm, Martin; Seitsonen, A. P.; Kirchner, B. (J. Phys. Chem. B)

Digitale Medien in Schule und Alltagswelt. Zur Verbindung von formalen und informellen Lernprozessen - Herzig, Bardo; Grafe, S. (Medienbildung in neuen Kulturräumen: Aufgaben, Adressaten, Ansätze)